2017
DOI: 10.5430/jnep.v7n12p10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of internet use for health information and internet addiction on adolescents female high school’ health lifestyle

Abstract: Background and objective: There is not enough evidence linking attitudes toward using the Internet to gather health information and adolescents' lifestyles. The objective of this study is to assess the effect of Internet use for gathering health information and Internet addiction on adolescents' health lifestyles in Saudi Arabia. Methods: A descriptive correlational cross-sectional design was utilized to collect data from a convenience sample of 456 high-school-aged female adolescents, who completed self-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Also, the study indicated that Internet addiction had a significant relationship with poor sleep and depression. [16,17] A study conducted in KSA found that 38.4% and 2.1% of the participants were categorized as moderate to severe internet addiction respectively, while 64.6% of them suffering from depression compared by 35.4% without depressive symptoms. [18] In Egypt many studies found that 17% of teenagers used Facebook and 46% of them agreed that Facebook is an important part of their social life.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the study indicated that Internet addiction had a significant relationship with poor sleep and depression. [16,17] A study conducted in KSA found that 38.4% and 2.1% of the participants were categorized as moderate to severe internet addiction respectively, while 64.6% of them suffering from depression compared by 35.4% without depressive symptoms. [18] In Egypt many studies found that 17% of teenagers used Facebook and 46% of them agreed that Facebook is an important part of their social life.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies referred both to gender differences in health-related use of the Internet [15] or social media [16] and to health-related Internet use by women in particular. [17,18] However, these studies focused primarily on health-related Internet behavior at a specific time point without addressing its sustained use.…”
Section: Introductionmentioning
confidence: 99%